2017
DOI: 10.1002/jbm.a.36126
|View full text |Cite
|
Sign up to set email alerts
|

The effect of riboflavin/UVA cross‐linking on anti‐degeneration and promoting angiogenic capability of decellularized liver matrix

Abstract: Weak mechanical property and unstable degradation rate limited the application of decellularized liver matrix in tissue engineering. The aim of this study was to explore a new method for improving the mechanical properties, anti-degeneration and angiogenic capability of decellularized liver matrix. This was achieved by a novel approach using riboflavin/ultraviolet A treatment to induce collagen cross-linking of decellularized matrix. Histological staining and scanning electron microscope showed that the diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Considering that riboflavin/UVA treatment can act as a cross-linking system able to improve the biomechanical Frontiers in Bioengineering and Biotechnology frontiersin.org rigidity of decellularized scaffolds (Xiang et al, 2017) and corneas (Aslanides et al, 2016), it might also have a positive effect on fibrin-agarose scaffolds. However, the correlation analysis revealed the opposite behavior, showing that riboflavin/UVA exposure on plasma did not preserve coagulation factor levels.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that riboflavin/UVA treatment can act as a cross-linking system able to improve the biomechanical Frontiers in Bioengineering and Biotechnology frontiersin.org rigidity of decellularized scaffolds (Xiang et al, 2017) and corneas (Aslanides et al, 2016), it might also have a positive effect on fibrin-agarose scaffolds. However, the correlation analysis revealed the opposite behavior, showing that riboflavin/UVA exposure on plasma did not preserve coagulation factor levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cross-linking by agents such as glutaraldehyde and proanthocyanidins is an effective method to improve the mechanical property of dentine collagen [6,60,61] due to the generation of additional collagen cross-links by covalent and hydrogen bonds [9][10][11]. Hence, the present research intended to determine whether or not the molecular structure of dentine collagen changed after the G4-PAMAM-COOH pre-treatment and ascertain the mechanism of interaction between G4-PAMAM-COOH and collagen, which contributed to the evaluation of the effect of G4-PAMAM-COOH on the mechanical capacity of dentine collagen.…”
Section: Discussionmentioning
confidence: 99%
“…For many solid organs and tissues, canulating and perfusing the primary artery is one of the best approaches. The kidney is perfused through the renal artery [ 148 , 164 , 243 ], the liver through the portal vein and/or the hepatic artery [ 169 , 245 ], the pancreas through the splenic vein [ 99 ], the uterus through the uterine artery [ 153 ], and the corpus cavernosum through the cavernosal artery [ 157 ]. Other organs that are typical decellularized through chemical baths can be decellularized if there is a need to keep the structure intact, such as perfusing the superior mesenteric artery to decellularize the jejunum [ 144 ], the common carotid artery for the cervical esophagus [ 246 ], and the ureter for bladders [ 185 ].…”
Section: Methods Of Preparing Decmmentioning
confidence: 99%